Brain Abnormalities and Epilepsy in Patients with Parry-Romberg Syndrome - De la Garza-Ramos, C.; Jain, A.; Montazeri, S.A.; Okromelidze, L.; McGeary, R.; Bhatt, A.A.; Sandhu, S.J.S.; Grewal, S.S.; Feyissa, A.; Sirven, J.I.; Ritaccio, A.L.; Tatum, W.O.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Parry-Romberg syndrome is a rare disorder characterized by progressive hemifacial atrophy. Concomitant brain abnormalities have been reported, frequently resulting in epilepsy, but the frequency and spectrum of brain involvement are not well-established. This study aimed to characterize brain abnormalities in Parry-Romberg syndrome and their association with epilepsy.MATERIALS AND METHODS: This is a single-center, retrospective review of patients with a clinical diagnosis of Parry-Romberg syndrome and brain MR imaging. The degree of unilateral hemispheric atrophy, white matter disease, microhemorrhage, and leptomeningeal enhancement was graded as none, mild, moderate, or severe. Other abnormalities were qualitatively reported. Findings were considered potentially Parry-Romberg syndrome–related when occurring asymmetrically on the side affected by Parry-Romberg syndrome.RESULTS: Of 80 patients, 48 (60%) had brain abnormalities identified on MR imaging, with 26 (32%) having abnormalities localized to the side of the hemifacial atrophy. Sixteen (20%) had epilepsy. MR imaging brain abnormalities were more common in the epilepsy group (100% versus 48%, P < .001) and were more frequently present ipsilateral to the hemifacial atrophy in patients with epilepsy (81% versus 20%, P < .001). Asymmetric white matter disease was the predominant finding in patients with (88%) and without (23%) epilepsy. White matter disease and hemispheric atrophy had a higher frequency and severity in patients with epilepsy (P < .001). Microhemorrhage was also more frequent in the epilepsy group (P = .015).CONCLUSIONS: Ipsilateral MR imaging brain abnormalities are common in patients with Parry-Romberg syndrome, with a higher frequency and greater severity in those with epilepsy. The most common findings in both groups are white matter disease and hemispheric atrophy, both presenting with greater severity in patients with epilepsy.ASMantiseizure medicationECDSen coup de sabreEEGelectroencephalogramIQRinterquartile rangePRSParry-Romberg syndromeWMDwhite matter disease